2023
DOI: 10.1038/s41598-023-44523-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous and intermittent blood flow restriction deep-squat training on thigh muscle activation and fatigue levels in male handball players

Yan Wang,
Zhiyuan Li,
Che Tongtong
et al.

Abstract: We aimed to investigate acute changes before and after low-intensity continuous and intermittent blood flow restriction (BFR) deep-squat training on thigh muscle activation characteristics and fatigue level under suitable individual arterial occlusion pressure (AOP). Twelve elite male handball players were recruited. Continuous (Program 1) and intermittent (Program 2) BFR deep-squat training was performed with 30% one-repetition maximum load. Program 1 did not include decompression during the intervals, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Our second finding was that hip extensors (hamstrings, gluteus maximus, and gluteus medius) adapted more at slower speeds (80 bpm) than at faster speeds (140 bpm). This previous outcome indicates that BFR with lower speed makes muscles more engaged, which is required for stability during the activity (Wang et al, 2023). This principle of hip extensor activity is similar to Liu et al, (2008), who found that hip extensors (gluteus maximus, gluteus medius, vastus, hamstrings, gastrocnemius, and soleus) are the main muscles that aid stability and forward progression during walking at any speed.…”
Section: Discussionsupporting
confidence: 81%
“…Our second finding was that hip extensors (hamstrings, gluteus maximus, and gluteus medius) adapted more at slower speeds (80 bpm) than at faster speeds (140 bpm). This previous outcome indicates that BFR with lower speed makes muscles more engaged, which is required for stability during the activity (Wang et al, 2023). This principle of hip extensor activity is similar to Liu et al, (2008), who found that hip extensors (gluteus maximus, gluteus medius, vastus, hamstrings, gastrocnemius, and soleus) are the main muscles that aid stability and forward progression during walking at any speed.…”
Section: Discussionsupporting
confidence: 81%
“…Wang et al. ( 31 ) found that continuous compression during BFRE can improve muscle functional capacity more than intermittent compression, but higher fatigue phenomena also occur. In contrast, although intermittent BFRE can also bring fatigue, the recovery speed is faster.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance-based BFR training may increase skeletal muscle strength ( Centner et al, 2019 ). In addition, BFR training is less load-bearing, generates less mechanical strain, and induces increased metabolic stress ( Pearson and Hussain, 2015 ; Wang et al, 2023 ). The current American Heart Association recommends that the load of RT for the rehabilitation of patients with cardiovascular disease should be reduced (30% of the single maximal load for the upper extremity and 50%–60% of the single maximal load for the lower extremity), as this will not only lead to improved muscle strength and endurance but also not result in excessive increases in blood pressure or other adverse cardiovascular outcomes ( Kambič et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%